Effect of pseudopotential choice on the calculated electron and phonon band structures of palladium hydride and its vacancy defect phases. (1st January 2021) - Setayandeh, Samaneh Sadat; Gould, Tim; Vaez, Aminollah; Gray, Evan
Abstract: Density functional theory is increasingly used to predict and understand the properties of hydrogen storage materials. Many such calculations have been performed for various real and hypothetical palladium hydrides, yet despite excellent agreement on electron band structures, significant disparities persist in relation to phonon band structures and critical matters such as dynamic stability of alternative structures. Some disparities may arise because of differing computation approaches between researchers. Therefore in this work a systematic approach was followed to compare calculated electron and phonon band structures for four palladium hydrides: PdH and Pd3 VacH4 (the superabundant vacancy phase) assuming that octahedral ( oct ) or tetrahedral ( tet ) lattice interstices are occupied by H, with six commonly used calculation schemes based on the local density approximation and the generalised gradient approximation, within the harmonic approximation. Of the twenty-four combinations tested, seven are new to the literature. Excellent agreement was found between the calculation schemes for the electron band structures of all four crystal structures. The position regarding phonons is much less satisfactory, however, and highlights the sensitivity of phonon properties to the calculated lattice constants. None of the calculation schemes could reproduce the measured phonon energy gap of PdH( oct ) and it is necessary to include anharmonicity of the H potential to obtain realistic results. The calculated lattice constants of PdH( tet ) were larger than any observed in experiments, although the structure is dynamically stable. All six calculation schemes predicted dynamic instability for Pd3 VacH4 ( oct ), although the calculated lattice constant agreed with the estimated zero-temperature experimental value. This structure requires new calculations accounting for anharmonicity. The calculated lattice constant for Pd3 VacH4 ( tet ) was larger than any experimental value, so this alternative, while dynamically stable, is certainly not observed. Graphical abstract: Image 1 Highlights: Systematic test of pseudopotential choice for DFT calculations of MH systems. Four PdH x structures considered: PdH( oct ); PdH( tet ); Pd3 VacH4 ( oct ); Pd3 VacH4 ( tet ). Six DFT schemes employed: LDA, PBE and PBESol, with USPP and PAW pseudopotentials. Lattice constants calculated for tet polymporphs have not been found experimentally. Pd3 VacH4 ( oct ) is dynamically unstable in the harmonic approximation.